(untitled) - Simmons, George F. (Tokyo, 1963)
Content: Part one: Topology, Chapter 1 Sets and Functions, Chapter 2 Metric Spaces, Chapter 3 Topological Spaces, Chapter 4 Compactness, Chapter 5 Separation, Chapter 6 Conectedness, Chapter 7 Approximation; Part 2 Operators, Chater 8 Algebraic systems, ...
Keywords: Toán giải tích,Mathematical analysis